Minat Belajar Mahasiswa terhadap Pembelajaran Chookai - Arianingsih, Anisa; Setiana, Soni Mulyawan (Journal of Japanese Language Education and Linguistics, 2018)
ABSTRACT This research aims to discover the extent of students’ learning interest in studying Chookai IV in Japanese Department Unikom. The method used is descriptive analysis. Data collection was done by distributing questionnaires and literature study. The samples in this research were students of semester IV in the academic year of 2017/2018. The results showed that the student’s interest in following Chookai IV lecture was high in terms of interest with 96.9%, the pleasure with 84.4%, and the enthusiasm to follow the lecture of Chookai IV by 75%. In addition, the students’ interest to do the job well and on time was high. However, the interest of students to always be present in the lectures and interest to repeat the material that has been studied is still not good. Therefore, lecturers need to conduct a deeper evaluation related to the method of assignment before and after the learning in order to improve students’ learning outcomes. Keywords: learning interest, student, learning, Chookai